Urban and regional transportation modeling essays in honor of David Boyce (New dimensions in networks, 2004)
Honoring David Boyce for his legendary contributions to the fields of transportation modeling and regional science, the chapters in this festschrift highlight and analyze state-of-the-art and state-of-the-practice methodologies and theories in transportation modeling, regional and urban planning